1996
DOI: 10.1182/blood.v87.3.1075.bloodjournal8731075
|View full text |Cite
|
Sign up to set email alerts
|

Consistent amounts of acute leukemia-associated P190BCR/ABL transcripts are expressed by chronic myelogenous leukemia patients at diagnosis

Abstract: Supported by grants from MURST, CNR (Progetto jinalizzato FATMA Sp I , and Progettojnalizzato ACRO Sp 4, Rome), Regione Campania, AIRC (Milan) and Agensud. A.D. is supported by an AIDS fellowship of Minister0 della Sanita.Address reprint requests to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 14 publications
4
26
0
3
Order By: Relevance
“…In some of our samples multiple intermediate PCR products were produced which were most probably the result of alternative splicing of the BCR-ABL pre-mRNA. We believe that the p190 transcripts in our samples as well as in the samples, examined by others (Saglio et al, 1996;van Rhee et al, 1996), were the result of alternative splicing. Six of the co-expressing patient samples included in this study were also analysed by interphase FISH using BCR and ABL probes, and in each case only a single Ph chromosome was seen per cell (data not shown).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…In some of our samples multiple intermediate PCR products were produced which were most probably the result of alternative splicing of the BCR-ABL pre-mRNA. We believe that the p190 transcripts in our samples as well as in the samples, examined by others (Saglio et al, 1996;van Rhee et al, 1996), were the result of alternative splicing. Six of the co-expressing patient samples included in this study were also analysed by interphase FISH using BCR and ABL probes, and in each case only a single Ph chromosome was seen per cell (data not shown).…”
Section: Discussionsupporting
confidence: 51%
“…The expression of p190 transcripts in chronic-phase CML patient samples has been reported previously (Saglio et al, 1996;van Rhee et al, 1996). In their studies co-expression of p190-and p210-encoding BCR-ABL transcripts occurred in >70% of patients with chronic-phase CML.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Dhingra et al (1991) have speculated that co-existence of P190 BCR-ABL and P210 BCR-ABL type mRNAs might correlate with disease progression. However, Saglio et al (1996) have recently reported that co-expression of CML and ALL type mRNA in CML is actually very frequent and is not correlated with disease progression.…”
Section: Discussionmentioning
confidence: 99%